Acaricidal Activity of Biosurfactants Produced by Serratia ureilytica on Tetranychus urticae and Their Compatibility with the Predatory Mite Amblyseius swirskii - Arnoldo Wong-Villareal; Esaú Ruiz-Sánchez; Marcos Cua-Basulto; Saúl Espinosa-Zaragoza; Avel A. González-Sánchez; Ernesto Ramos-Carbajal; Cristian Góngora-Gamboa; René Garruña-Hernández; Rodrigo Romero-Tirado; Guillermo Moreno-Basurto; Erika P. Pinson-Rincón (Microbiology Research)
This study evaluated the acaricidal effects of biosurfactants produced by Serratia ureilytica against the two-spotted spider mite Tetranychus urticae and their compatibility with the predatory mite Ambliseus swirski. The biosurfactants were obtained via liquid cultures of the bacterial strains. In the laboratory, T. urticae was exposed via acaricide-immersed leaves and A. swirskii via acaricide-coated glass vials. In the greenhouse, mite-infested plants were sprayed with the biosurfactants. In the laboratory, biosurfactants produced by S. ureilytica NOD-3 and UTS exhibited strong acaricidal activity, causing 95% mortality in adults and reducing egg viability by more than 60%. In the greenhouse trial, all biosurfactants significantly suppressed T. urticae populations at all evaluated periods (7, 14, and 21 days post-application). Gas chromatography–mass spectrometry (GC-MS) analysis of the biosurfactants identified several fatty acids, including hexadecanoic acid, pentanoic acid, octadecanoic acid, decanoic acid, and tetradecanoic acid, as well as the amino acids L-proline, L-lysine, L-valine, and glutamic acid. These fatty acids and amino acids are known structural components of lipopeptides. Furthermore, the bioinformatic analysis of the genomes of the three S. ureilytica strains revealed nonribosomal peptide synthetase (NRPS) gene clusters homologous to those involved in the biosynthesis of lipopeptides. These findings demonstrate that S. ureilytica biosurfactants are promising eco-friendly acaricides, reducing T. urticae populations by >95% while partially sparing A. swirskii.